Analisis Faktor-faktor yang Memengaruhi Keputusan Pembelian Minyak Goreng Merek Bimoli di Pasar Swalayan Kota Semarang - Purnamasidhi, Naura Adristy; Mariyono, Joko; Prasetyo, Edy (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
This study aims to describe the characteristics of consumers of Bimoli brand cooking oil in supermarkets in Semarang City and analyze the factors that influence their purchasing decisions. The research was conducted from June to August 2025 in five supermarkets representing Semarang City, namely ADA Swalayan Setiabudi, ADA Swalayan Majapahit, Super Indo Imam Bonjol, Super Indo Siliwangi, and Super Indo Sukarno Hatta. The research method used a survey with a quota sampling technique (non-probability sampling) to collect data from 150 Bimoli consumers, with samples taken using a purposive sampling technique. The independent variables included product price (X1), product quality (X2), brand image (X3), packaging (X4), fanaticism (X5), and number of family members (X6), while the dependent variable was purchase decision (Y). Primary and secondary data were analyzed using descriptive analysis and logistic regression with the help of SPSS, including validity and reliability tests, as well as model testing using the Omnibus Test, Likelihood test, Overall Model Fit test, Hosmer and Lemeshow test, coefficient of determination test, and Wald test. The results of the study show that the majority of respondents are women (76%), aged 26-30 years (62%), with a bachelor's degree, working as employees, with a middle income (42%), and purchasing 2 L refills. The results of the logistic analysis reveal that product quality, brand image, packaging, and fanaticism has a significant positive effect on purchasing decisions, while product price and number of family members have no significant effect.